Surgical anatomy of the nasopharynx - Tang, Ing Ping; Prepageran, Narayanan; Zul Izhar, Mohd Ismail (Academic Press Elsevier, 2020)
This chapter introduces the surgical anatomy of the nasopharynx. Surgical anatomy of the nasopharynx is important for understanding nasopharyngeal diseases, especially malignancy. As the anatomy at this region is complicated and involves many important structures, great care should be emphasized. This chapter describes the anatomy of nasopharynx with a focus on important surgical landmarks.